A novel sensor for the selective monitoring of trace ytterbium ions using an agarose-based optical membrane. Issue 41 (20th September 2022) - Amin, Alaa S.; El-Feky, Hesham H.; Hassan, Nader
Abstract : The immobilized optical sensor preparation and its measurement procedure. Abstract : A novel highly selective sensitive optical sensor was prepared via the chemical immobilization of β-2-hydroxybenzyl-5-bromo-2-hydroxyazastyrene (HBBHAS) on an epoxy-activated agarose membrane pieces. The absorbance variation of the immobilized azastyrene film on agarose upon the addition of 1.5 × 10 −5 M aqueous solutions of La 3+, Y 3+, Al 3+, Sc 3+, Sm 3+, Eu 3+, Lu 3+, Fe 3+, Ce 3+, Cr 3+, S2 O3 2−, Tb 3+, Mn 2+ and KIO3 revealed substantially higher changes for the Yb 3+ ion compared to the other considered ions. Thus, using HBBHAS as an appropriate ionophore, a selective optical sensor for Yb 3+ was prepared via its chemical immobilization on a transparent agarose membrane. The effects of pH, reagent concentration, and time duration of the reaction of immobilizing the reagent were examined. A distinct change in the maximum absorbance of the reagent was established on contact of the sensing membrane with Yb 3+ ions at pH = 4.25. For the membrane sensor, a linear relationship was observed between the variation in membrane absorbance (Δ A ) at 424 nm and Yb 3+ concentrations in the range of 4.75 × 10 −5 to 6.20 × 10 −10 M with a detection limit of 1.9 × 10 −10 M for Yb 3+ . The effects of some potentially interfering ions on the assessment of Yb 3+ were analyzed, and no substantial interference was found. The sensor showed a short response time and decent durability with no reagent leaching. The recovery of Yb 3+ ions from the sensor material was performed using 0.3 M HNO3 and its response was reversible and reproducible with RSD ≥ 1.95%. This study reports a non-toxic, economical, stable, accurate, easy-to-use, and novel optical sensor material to assess Yb 3+ in synthetic and environmental water samples.